KRITERIA IKTIKAD TIDAK BAIK DALAM PROSES PENDAFTARAN MEREK - Tahasak Sahay (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2010)
Adishonest intention is one of the reasons for the authorities to refuse an appeal for trademark registration because the appeal is dishonestly purposed and there is applicants' intention to sponge on, to imitate, and to copy the fame of others'trademarks for their benefit. This will inflict a loss upon others and bring about an unfair competitive condition, deceiving and misleading consumers. The absence of a stipulation informing appropriately the criteria of dishonest intentions in the process of trademark registration will bring about many interpretations in its legal implementation. The examination of dishonest intentions in trademark registration is carried out in the phase of substantive examination with the following criteria: (a) Resembling or imitating totally for goods/services that are not of the same types that have been registered or the registration appeal of which has been previously proposed, (b) Resembling or imitating totally other logogram designs that have been registered or the registration appeal of which has been previously proposed, (c) Resembling and imitating totally the methods/shapes of writings or inventive words belonging to others that have been registered or the registration appeal of which has been previously proposed.